RIG-I activation by a designer short RNA ligand protects human immune cells against dengue virus infection without causing cytotoxicity - Fink, Katja (2019)
Virus-derived double-stranded RNA (dsRNA) molecules containing a triphosphate group at the 5′ end are natural ligands of retinoic acid-inducible gene I (RIG-I). The cellular pathways and proteins induced by RIG-I are an essential part of the innate immune response against viral infections. Starting from a previously published RNA scaffold (3p10L), we characterized an optimized small dsRNA hairpin (called 3p10LG9, 25 nucleotides [nt] in length) as a highly efficient RIG-I activator. Dengue virus (DENV) infection in cell lines and primary human skin cells could be prevented and restricted through 3p10LG9-mediated activation of RIG‐I. This antiviral effect was RIG-I and interferon signal dependent. The effect was temporary and was reversed above a saturating concentration of RIG-I ligand. This finding revealed an effective feedback loop that controls potentially damaging inflammatory effects of the RIG-I response, at least in immune cells. Our results show that the small RIG-I activator 3p10LG9 can confer short-term protection against DENV and can be further explored as an antiviral treatment in humans.